Line following robots on factory floors: Significance and Simulation study using CoppeliaSim. Issue 1 (January 2021) - Oswal, Saharsh; Saravanakumar, D
Abstract: Line following robots has been around for many years now. Research and development of these robots have been keenly studied and examined for many industrial applications. Line following robots can provide maximum effectiveness to in-house transportation of jobs inside a factory, which is traditionally done by forklifts and different types of cranes. These traditional methods are high maintenance and extremely unsafe for the employees. This paper presents the design, assembly and dynamic simulation of a line following robot integrated with a proximity sensor for collision avoidance and vision sensors for line tracking. The model is designed using Autodesk Inventor 2018 and the assembly and simulation is carried out using CoppeliaSim software. This simulation study intends to provide significance of the implementation of such robots on a factory floor, which can cover a path of distance 10 meters in approximately 8 seconds.